Zonasi System In Admission of New Student and The Impact on The Psychological Condition of Students - Syamsul Bachri Thalib; Tarmizi Thalib; Mustafa; Musawwir (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine how well the zonasi system in new student admissions (PPDB) is. This achievement stems from the respondents' knowledge of the zonasi system's goals, advantages, and disadvantages. Furthermore, respondents' level of satisfaction and anxiety in dealing with PPDB is also analyzed. The respondents in this study were 250 students from 7 different school districts. The data obtained were analyzed quantitatively, descriptive, and regression. The results of this study indicate that the zonasi system was implemented appropriately. In principle, there is no difference between the new and old systems. Therefore, it is believed to encourage students to study harder. The level of student satisfaction tends to be high, and anxiety during PPDB tends to be low; the effect between the two was significant (r=-0.141; p <0.05). This study suggests the need for mapping the zones of state schools. Hence, there are no students outside the state school zone, considering the sudden transfer of students due to changes in assignments and parents' addresses, the need for potential academic tests as a reference for guidance and counseling teachers in providing guidance and counseling services; furthermore, the need to increase the number of new schools with state status.